2016
DOI: 10.3346/jkms.2016.31.10.1560
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Subclass Deficiencies in Adult Patients with Chronic Airway Diseases

Abstract: Immunoglobulin G subclass deficiency (IgGSCD) is a relatively common primary immunodeficiency disease (PI) in adults. The biological significance of IgGSCD in patients with chronic airway diseases is controversial. We conducted a retrospective study to characterize the clinical features of IgGSCD in this population. This study examined the medical charts from 59 adult patients with IgGSCD who had bronchial asthma or chronic obstructive pulmonary disease (COPD) from January 2007 to December 2012. Subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…A Korean group reported that amongst adult patients with asthma or COPD, who were found to have an IgG subclass deficiency, nearly 30% also met ≥2 criteria on a screening test of 10 clinical signs of PIDD. This subgroup had significantly higher numbers of hospitalizations (p = 0.012) and exacerbations of asthma or COPD (p < 0.001), and lower FEV1 (p = 0.036) than the group who did not have warning signs of PIDD [17].…”
Section: Pidd and Airway Diseasesmentioning
confidence: 86%
“…A Korean group reported that amongst adult patients with asthma or COPD, who were found to have an IgG subclass deficiency, nearly 30% also met ≥2 criteria on a screening test of 10 clinical signs of PIDD. This subgroup had significantly higher numbers of hospitalizations (p = 0.012) and exacerbations of asthma or COPD (p < 0.001), and lower FEV1 (p = 0.036) than the group who did not have warning signs of PIDD [17].…”
Section: Pidd and Airway Diseasesmentioning
confidence: 86%
“…Higher hyperreactivity correlated with a defect in IgA [80]. A correlation between IgG subclass deficiency and asthma has recently been highlighted [81].…”
Section: Asthma and Copdmentioning
confidence: 97%
“…Plebani et al [62] reported that lower respiratory tract infections were most frequent in patients with XLA and that 78% of patients had bronchitis. In milder forms of humoral immunodeficiency, recurrent bronchitis manifests in IgG3 deficiency, the most common subclass deficiency (88.1%), and IgG4 deficiency (15.3%) [63]. IgG subclass deficiency is characterized by exacerbation-prone phenotypes, decline in lung function, and subsequent poor prognosis [63].…”
Section: Bronchitismentioning
confidence: 99%
“…In milder forms of humoral immunodeficiency, recurrent bronchitis manifests in IgG3 deficiency, the most common subclass deficiency (88.1%), and IgG4 deficiency (15.3%) [63]. IgG subclass deficiency is characterized by exacerbation-prone phenotypes, decline in lung function, and subsequent poor prognosis [63]. Although these patients did not manifest evidence of pneumonic infiltration on chest x-ray, they were diagnosed as having recurrent bronchitis, which was defined as ≥3 episodes of acute bronchitis per year [63].…”
Section: Bronchitismentioning
confidence: 99%
See 1 more Smart Citation